E2.1 Using appreciative inquiry to explore the factors which contribute to a positive educational environment in a tertiary paediatric setting. (4th October 2017) - Al-Yassin, A; Long, A
Abstract : Background: In the UK both general and subspeciality paediatric trainees undertake attachments in highly-specialised tertiary hospitals. The cases, investigations and procedures here may be unfamiliar to the general trainee. This may lead to trainee dissatisfaction, mismatched trainee-trainer expectations and a perceived lack of educational opportunities. With the "Shape of training" review (reshaping postgraduate training in the UK to focus on more general themes) this issue may become more prominent. We wanted to explore the factors that contribute to a positive educational environment and training experience and how this could be improved in our tertiary setting. Methods: GMC and London school of paediatrics survey data was examined to find areas of practice where our organisation received less-than optimal scores. These areas were then explored using observational work and semi-structured interviews with trainees. Appreciative inquiry methodology (Cooperrider 1990) was used to identify areas of perceived best practice and consider how these could be promoted and disseminated to build on the potential of the organisation (4D Model: Discover, Dream, Design, Deploy). Results: Twelve best-practice themes were identified (1) Manage expectations by acknowledging the challenges (2) Educational contracting to identify learning needs and opportunities (3) Creative educational supervision (4) Centralised teaching events (5) Signpost learning opportunities including non-clinical (6) Curriculum mapped pan-hospital teaching programmes (7) Local faculty groups with trainee representation (8) Inter-professional learning (9) Pastoral support systems (10) Cross-over weeks to increase clinical exposure (11) Adequate clinical supervision (12) Rota design to include teaching and clinic time. Conclusions: Through appreciative inquiry, trainees identified methods of best practice which have the potential to enhance their educational environment and training experience. These included trainee, trainer and organisational factors.